Setting standard levels for some skill capabilities as an indicator to the selection of basketball team players at a secondary school (16-18) years old males - a study for the region of batna (oum el bouaghi, Khenchela, Batna). - youcef khodja, houssem; merabet, messaoud (sports creativity, 2025)
This study aimed to find out the possibility of setting standard levels for some of the Skill abilities as an indication of selection of players in school basketball teams in the secondary school. The Batna region )oum el bouaghi ,khenchela ,batna), we have used the descriptive approach in the analytical method ,the study sample included 120 basketball players distributed into 12 team acquiring the first four ranks in each state ,we have used a standardized test battery, that made either of a group of academics specialized in basketball from all over the Arab world, in addition to coaches of the excellent basketball department in Algeria. The study counseled: determing standardized and reliable skills levels and indicator for the selection of school basketball teams and Measuring the skill level of the players, which wad average according to the levels results